Correlation analysis between preoperative odontoid incidence and clinical outcomes 2 years after anterior cervical discectomy and fusion - Yan Gong; Hao Liu; Yanchi Gan; Jiahui He; Zelin Zhou; Hang Zhuo; Yu Liu; De Liang; Hui Ren; Xiaobing Jiang; Zhaojun Cheng (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study presents a novel odontoid parameter, the odontoid incidence (OI), to examine the correlation between OI on preoperative cervical sagittal radiographs and 2-year clinical outcomes following short-segment anterior cervical discectomy and fusion (ACDF) in patients with cervical spondylotic myelopathy (CSM). Methods A retrospective analysis of the clinical data of 87 patients with CSM who underwent ACDF surgery from January 2018 to December 2023 was conducted. The patients were categorized into a larger OI group (44 patients, OI > 12.62°) and a smaller OI group (43 patients, OI ≤ 12.62°) on the basis of the median cervical sagittal OI prior to surgery. The postoperative follow-up duration was 2 years. Cervical sagittal parameters were assessed on lateral cervical spine radiographs both preoperatively and postoperatively. Additionally, the Japanese Orthopedic Association (JOA), neck disability index (NDI), and visual analog scale (VAS) scores were documented for each patient before surgery and at the final 2-year postoperative follow-up. Results Compared with those in the preoperative period, the T1 slope, C2‒C7 Cobb angle, sagittal segmental angle (SSA), and C0‒C2 Cobb angle significantly improved in 87 patients with cervical spondylosis (P < 0.05). At the 2-year postoperative follow-up, all patients exhibited significant improvements in JOA, NDI, and VAS scores compared with the preoperative values (P < 0.05). No statistically significant difference was observed in the preoperative or baseline data between the larger OI group and the smaller OI group (P > 0.05); however, a statistically significant difference was noted in the postoperative SSA between the two groups (P < 0.05). A statistically significant difference was observed in the VAS score and NDI score at the final follow-up between the two groups (P < 0.05), as well as in the improvement in the JOA score and VAS score (preoperative score minus the final follow-up score), between the two groups (P < 0.05). The results of the Pearson correlation analysis indicated a negative correlation between the preoperative OI score and the VAS and NDI scores at the final postoperative follow-up (P = 0.012, r = − 0.268) (P = 0.028, r = − 0.236). Conclusion In ACDF, the preoperative OI of patients with CSM was negatively correlated with the VAS and NDI scores at the final postoperative follow-up; Larger preoperative OI corresponded to lower VAS and NDI scores at the final follow-up, leading to comparatively improved 2-year clinical outcomes.